Immune response and protection efficacy of formalin-killed vaccines against Streptococcus iniae in four-finger threadfin Eleutheronema tetradactylum - Shi, Yin-Ze (Journal of fish diseases, 2024)
© 2024 John Wiley & Sons Ltd.